21st century migration and work : a case study on international migrant integration in the Finnish labor market - Stewart, John (2020)
This paper provides a deeper understanding of the integration process of international migrants in the Finnish labor market and its future labor market implications. A historical overview of immigration to Finland and the effects of globalization is presented and will provide readers with a greater understanding of how Everett Lee’s Push-Pull Theory plays out with Finland as a more recent destination for international migration. Utilizing the corresponding concepts of Pierre Bourdieu and Robert Putnam’s similar, yet unique, explanations of social capital, along with knowledge, skills and abilities (KSAs), readers will be able to assess the variables that impact international migrant integration in the Finnish labor market along with the two benefits of successful integration including the “brain gain” related to human capital flight and remittances. Through the quantitative and qualitative responses of 205 online survey respondents who are international migrants in the Finnish labor market from 65 countries, readers will hear from a diverse array of both employed and unemployed perspectives providing a holistic overview of the labor market integration process. With the culmination of this knowledge, readers can begin to assess how and what has and has not been achieved in the past 5 years of international migrants entering the Finnish labor market and future implications on labor market integration in Finland. This paper can be a starting point for additional research aiming to enhance Finnish labor market integration.